2012
DOI: 10.5254/rct.12.88935
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Mixing Conditions for Silica-Reinforced Natural Rubber Tire Tread Compounds

Abstract: The dump temperature and mixing interval between rubber, silica and silane coupling agent for silica-filled natural rubber (NR) tire tread compounds using bis-triethoxysilylpropyl tetrasulfide (TESPT) as silane were optimized. The dump temperature turns out to be the key parameter governing the properties of the silica-filled NR compounds. The increase in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
143
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(158 citation statements)
references
References 13 publications
13
143
0
2
Order By: Relevance
“…Therefore, the conductivity of the composites could be enhanced and the dielectric constant could be reduced if the CNT forms threedimensional networks in the rubber matrix, with minimal gaps between the CNT bundles. Silane coupling agent, particularly bis(triethoxysilylpropyl)tetrasulfide (TESPT), has been long applied to enhance filler dispersion (CB, CNT and silica) in NR and ENR matrices [5]. It was found that incorporation of TESPT significantly improved dispersion of CNT in NR and ENR matrices and improved the optimal conductivity by about two orders of magnitude relative to composites without TESPT [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the conductivity of the composites could be enhanced and the dielectric constant could be reduced if the CNT forms threedimensional networks in the rubber matrix, with minimal gaps between the CNT bundles. Silane coupling agent, particularly bis(triethoxysilylpropyl)tetrasulfide (TESPT), has been long applied to enhance filler dispersion (CB, CNT and silica) in NR and ENR matrices [5]. It was found that incorporation of TESPT significantly improved dispersion of CNT in NR and ENR matrices and improved the optimal conductivity by about two orders of magnitude relative to composites without TESPT [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, improved filler-rubber interactions not only enhance the conductivity of the rubber vulcanizates via improved filler dispersion, but also the reduce thickness of the rubber layer absorbed on filler surfaces. Table 6 indicates the bound rubber layer thickness (δ) calculated from Equation (5). It is clearly seen that the δ for ENR vulcanizates is less than for the NR vulcanizates, promoting lower φ c for the ENR composites.…”
Section: Electrical and Morphological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…But at a temperature above 160°C the silane starts to react with the elastomer to form premature crosslinks [3]. For silica-filled NR compounds with TESPT as coupling agent, a discharge temperature is recommended in the range of 135-150°C while a higher temperature leads to degradation of the NR [4]. All silanes with alkoxy functional groups may react with the silanol groups on the silica and so shield the silica surface to make it more hydrophobic [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is called ''pre-scorch'' and might cause the processability difficulties. [22,37] [38] Model compound studies were also carried out to investigate this ''pre-scorch'' reaction further. [34,35,39] By mixing only TESPT and squalene (which is a model substance of rubber), the average sulfur length of the silane decreases.…”
Section: -3-1 Introduction Of Silanementioning
confidence: 99%